How does spending change through retirement? - Rowena Crawford; Heidi Karjalainen; David Sturrock (Institute for Fiscal Studies (IFS), 2022)
Fuelled by changes to UK pensions policy over the last decade, most notably automatic enrolment into workplace pensions, an increasing number of people save for their retirement in defined contribution pension pots. Due to the end of compulsory annuitisation in 2015, known as 'Pension Freedoms', those saving in this way have a great deal of flexibility over the pace at which to withdraw income from their accumulated pension pot and how to vary this through their retirement. These changes have led to concerns around what the appropriate withdrawal rate of pension pots should be for retirees. Desired profiles of spending in retirement are a key ingredient in how fast funds should be withdrawn. Whether people prefer a constant, increasing or decreasing profile of spending through their retirement will affect the kind of income profile they should aim for. In this report, we shed light on this question by examining the spending patterns of current retirees in the UK using data from the Living Costs and Food Survey, from 2006 to 2018, which allows us to get a detailed picture of retired households' spending patterns. We consider how spending changes with age and how it relates to levels of income and saving among retirees. We also document how spending on different categories of goods and services changes with age. Finally, we consider how spending patterns differ between different types of household.
Keywords: 330; Privater Konsum; Rentner; Altersgruppe; Altersvorsorge; Großbritannien